Avaliação da atividade enzimatica de células imobilizadas de Aspergillus Oryzae IPT 301 para produção de frutooligossacarídeos em reator leito fixo - Cruz, Jardel Artiman Da (2022)
Fructooligosaccharides are low-caloric functional sugars with numerous benefits for human health. Their industrial synthesis primarily occurs in batch-mode reactors, utilizing microbial enzymes in solution to catalyze the transfructosylation reaction, with sucrose as the substrate. Of the enzymes that produce FOS, the FTase produced by the microorganism Aspergillus Oryzae IPT-301 stands out, exhibiting high enzymatic potential. However, the current batch process is slow and costly due to the inefficiency of enzyme recovery. Hence, the utilization of immobilized enzymes offers an advantage in biocatalyst reuse during the reaction process. This study proposes the continuous production of FOS in a continuous packed bed reactor (PBR) filled with the catalytic biomass of Aspergillus Oryzae IPT-301 immobilized with glutaraldehyde and encapsulated in calcium alginate gel for optimal enzymatic activity. The effect of volume flow rate, substrate concentration, and reaction temperature on enzymatic activity was evaluated, as well as the external mass transfer parameters, kinetic parameters, and operational stability of the biocatalyst in systems with and without recycle. The maximum enzymatic activity was achieved at a volumetric flow rate of 10 ml.min-1, temperature of 60°C, and substrate concentration of 400 g.L-1. The experimental data was best fitted to Hill's model, implying cooperation among the enzyme complex's active sites. The value of the external mass transfer coefficient (Kc= 1.84x10-11 m.s-1) indicates a low influence of mass transport on reaction development. After 10 hours of reaction, the system without recycle exhibited 100% enzymatic activity, while the system with recycle displayed a maximum activity of 300% of the activity without recycle. The implementation of the PBR reactor filled with glutaraldehyde cross-linked FTase encapsulated with calcium alginate gel demonstrated promising results for the production of fructooligosaccharides.